"Really present to bless": The sacrament of creation and a practical ethic of environmental care for the local church. (August 2019) - Smith, Joshua Paul
Anthropogenic climate change poses the greatest existential threat humans have ever faced as a species. Churches must find creative ways to confront this frightening new reality, but how are we to do so faithfully? The first half of the article explores the suggestion that a harmful modern worldview of "disenchantment" is partly to blame for our current environmental crisis, and that this perspective fails to account adequately for God's real presence "in, with, and under" creation. The article then offers a short theological "sketch" that considers how a more robust sacramental imagination might challenge pastors and congregations to think differently about the interlocking relationships between God, humanity, and creation. Finally, the second half of the article recommends three small, practical steps that serve as "living signs" of this sacramental creation theology when put into practice by local churches, beginning with our dinner tables.